The application of omics in ruminant production: a review in the tropical and sub-tropical animal production context - Ribeiro, D.M. (2021)
The demand for animal products (e.g. dairy and beef) in tropical regions is expected to increase in parallel with the public demand for sustainable practices, due to factors such as population growth and climate change. The necessity to increase animal production output must be achieved with better management and production technologies. For this to happen, novel research methodologies, animal selection and postgenomic tools play a pivotal role. Indeed, improving breeder selection programs, the quality of meat and dairy products as well as animal health will contribute to higher sustainability and productivity. This would surely benefit regions where resource quality and quantity are increasingly unstable, and research is still very incipient, which is the case of many regions in the tropics. The purpose of this review is to demonstrate how omics-based approaches play a major role in animal science, particularly concerning ruminant production systems and research associated to the tropics and developing countries